2016
DOI: 10.1590/s1806-92902016000200003
|View full text |Cite
|
Sign up to set email alerts
|

Intake, apparent digestibility, production, and composition of milk from cows fed diets with different sources of lipids

Abstract: -The objective of this study was to evaluate the effect of different sources of lipids in the diets of dairy cows on the intake and digestibility of nutritional fractions, and milk production and composition. The experiment was conducted in a 42-hectare area divided into eight paddocks covered with Brachiaria brizantha. Twelve crossbred Holstein × Zebu cows were distributed into three simultaneous 4 × 4 Latin squares. The treatments consisted of different sources of lipids, as follows: diet with no extra sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In general, diet DMI was higher than the 13.75 kg/d recommended by the NRC [8]. Murta et al [23] also observed DMI in crossbred Holstein/Zebu cows in lactation was higher than that recommended by NRC [8] and similar to that of this study. It was verified that with the inclusion of the cactus pear in the diet, the intake of NDFap by the animals decreased slightly, and the small variation was not sufficient to interfere with the rumination processes of the animals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In general, diet DMI was higher than the 13.75 kg/d recommended by the NRC [8]. Murta et al [23] also observed DMI in crossbred Holstein/Zebu cows in lactation was higher than that recommended by NRC [8] and similar to that of this study. It was verified that with the inclusion of the cactus pear in the diet, the intake of NDFap by the animals decreased slightly, and the small variation was not sufficient to interfere with the rumination processes of the animals.…”
Section: Discussionsupporting
confidence: 87%
“…The lowest rumination time with cactus pear inclusion is due to the high content of NFCs of high fermentation, thus increasing the rate of passage, decreasing the rumination time, and directly influencing the time spent idle. This change in behavior may favor the productive efficiency of the animal, with the decrease in maintenance requirements, especially when the ambient temperature is high [23]. The lower DM and NDF contents of the diets containing cactus pear, in addition to the higher digestibility of the diets in relation to the others evaluated, influenced the rumination characteristics of the cows, thus reducing the number of rumined bolus and the number of chews per bolus.…”
Section: Discussionmentioning
confidence: 99%
“…This difference can be explained by the fact that the NRC calculates these estimates based on Holstein cows in temperate regions. Murta et al [25] evaluated the productive performance of crossbred Holstein/Zebu cows from 100 to 150 days of lactation con suming different diets without restriction in the supply and verified that the DMI was about 33.0 g/kg of BW (15.7 kg/d). This value is similar to those that were observed in the pres ent study (15.88 kg/d).…”
Section: Discussionmentioning
confidence: 99%
“…Milk fat is the main component of total solids, so the reduction in fat content resulted in a lower percentage of total solids in the milk of cows consuming soybean oil. Murta et al (2016) reported a reduction in total milk content solids using soybean oil in the diet of lactating cows. Oliveira et al (2007) in a study testing high and low level of concentrate and lipid, reported that the addition of lipids reduced both fat and total milk solids.…”
Section: Discussionmentioning
confidence: 99%